Understanding Online Customers' Shopping Behavior and Driving Factors in Choosing Payment Options with Case Study in JABODETABEK Area - Sianturi, Ishak; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2017)
Abstract – E-commerce has been a phenomenal trend in Indonesia. There are a lot of traditional businesses have been transformed into e-commerce business. However, security issue is considered as a main barrier for this growth. In this research, the study is conducted to understand customers’ behavior and payment preference in e-commerce and how the perception of security towards payment option changes their expectation. The payment options studied in this research are based on current available payment options in Indonesia. The samples are gathered from Jakarta, Bogor, Depok, Tangerang and Bekasi areas by using online survey. The data gathered are related to information demographic (sex, age segment, marital status and socioeconomic status), online shopping behavior (shopping frequency, actual payment preference and payment expectation) and online payment transaction (perception on payment option, consideration factors in choosing payment option, priority factor in choosing payment option and perception on security in online shopping). After that, the data is grouped within certain categorical variables (segment demography, payment options, product categories, perception of payment, actual payment preference and payment expectation) and presented in contingency table. The presented data is mainly in the form of frequency distribution, proportion distribution and median value (for perception on payment option). Finally, the result is analyzed using contingency analysis. In understanding customers’ tendency to shop online, this research develops likeliness index based on weighted average of respondents’ shopping frequency. Likeliness index is used to compare customers’ tendency to shop online in different product categories. In understanding customers’ payment behavior, the proportion of actual payment preference is compared with the proportion of payment expectation. The same comparison is also analyzed for respondents who prioritize on security in order to understand the influence of security factor to customers’ payment behavior. In understanding the influence of customers’ perception towards payment option to their payment expectation, the median value of perception towards payment option is compared to the proportion of payment expectation. Last but not least, this research also analyses customers’ concerns towards security issue in payment by taking median value of worries rate towards security in online transaction and compare it with their awareness on security issues. This research finds that some product categories have higher tendency to shop online than the others. This will influence the pace of transformation from traditional business into e-commerce business in different product categories. This research also finds that different customers’ segment have different payment expectation in different product categories. Hence, e-commerce industry should adapt the availability of payment options to different target customers in different target market.  Considering the influence of security factor, this research finds that customers who prioritize on security have more preference and expectation towards certain type of payments in shopping online. However, this research cannot find the relation between customers’ perception on payment option itself with their payment expectation. This means that the perception of security and convenience of online transaction is not attached solely on the type of payment alone. Attaching other factors, such as product category and e-commerce website, is suggested in future research. There are also several other factors in considering customers’ payment choice, but the percentage is far less significant. Overall, customers are actually aware on many issues of security in online transaction, but it is not significantly worrying that could restrain them from shopping online. Keywords: e-commerce, online shopping, online commerce, online transaction, online payment